Structural analysis of an electrophoretically cryptic alcohol dehydrogenase variant from an Australian population of Drosophila melanogaster. - Chambers, G K (1981)
The existence of geographically widespread clines in genetic polymorphisms is persuasive evidence that the distribution of such genetic variance is determined by natural selection. However, when comparing clines it is important to be certain that identical structural genes are involved. We report a structural difference (proline-214 to serine) between the product of AdhF and an electrophoretically cryptic heat-stable variant isolated from an Australian natural population, ADH-FCh.D. ("fast" Chateau Douglas). The biochemical properties of this new variant must be taken into consideration when attempting to formulate a causal explanation of the maintenance of the three identified Adh alleles. Our data also show that the products of an AdhF and an AdhS allele in Drosophila melanogaster in an Australian population are identical over 70% of their amino acid sequences with their North American counterparts.